Extending the Technology Acceptance Model (TAM) to understand the perceived security and trust of users’ acceptance towards cryptocurrencies in Malaysia - Lee, Huey Teck (2022)
Cryptocurrencies' monetary value has been increasing steadily over the past twelve years, but their real-life application value has yet to be understood by the communities. The importance of the current study is to understand the comfort level and mental shift of the users in Malaysia towards the adoption and disruption of cryptocurrency in Malaysia. Therefore, the objective of this study is to be able to provide both theoretical and practical significances by integrating the concept of Perceived Trust Risk and Perceived Security Risk into the Technology Acceptance Model.